(untitled) (Research, Society and Development, 2021)
Over the years, pets began to be seen as members of families. Many tutors want to provide everything they can to ensure that all the needs of their animals, often called “children,” are met, which can be evidenced by maintaining demand levels in the industry, even in times of crisis. Thus, this research aimed to study the behavior of the PET market in the city of Solânea-PB, evaluating the supply and demand present in the region. Having as theoretical and bibliographic support, the definitions and theories of the study and strategic market planning, proceeded with the application of questionnaires intended for the consumer market, being tutors of at least one pet, and the offerers of the city. After analyzing the data, using a qualitative and quantitative approach, as the main results, there is a lack of variety in the offer of products / services as the main deficiency of providers reported by consumers, in addition to the demand for services such as diagnostic imaging, specialty care and hotel for dogs and cats, demonstrating business potential in the city. From the perspective of providers, the study pointed to some difficulties in the relationship with clients, especially regarding the valuation of services and the professional of Veterinary Medicine.